The importance of sodium and chloride ions for the development of DOCA-NaCl hypertension: a haemodynamic study - Zicha, J; Kunes, J; Jelínek, J; Leont'eva, G R; Govyrin, V A (Physiologia Bohemoslovaca, 1986)
The role of sodium and its accompanying anion for the development of DOCA-salt hypertension was studied in uninephrectomized DOCA-treated weanling Wistar rats which were fed a diet containing either sodium chloride or sodium bicarbonate (170 mmol/kg). The blood pressure was increased in both groups of rats with sodium overload as compared to rats fed a low-salt diet only. A decreased cardiac output and substantially elevated systemic resistance were demonstrated in both groups of rats with high sodium intake in comparison with rats kept on a low-salt diet. However, these haemodynamic changes were more pronounced in rats with sodium chloride overload than in animals with a high sodium bicarbonate intake. On the other hand, the rigidity of major arteries which was estimated as the pulse pressure/stroke volume ratio, was increased only in rats fed a diet with sodium chloride but not in rats with sodium bicarbonate overload. Thus high sodium intake was responsible for the changes of systemic resistance in DOCA-treated animals and its action was only slightly augmented by a high chloride intake. In contrast to this, the chloride overload seemed to be essential for the induction of increased arterial rigidity.
Keywords: inbrední kmeny potkanů; Rats, Inbred Strains; Sodium Bicarbonate; Rats; Hypertension; chloridy; hydrogenuhličitany; hydrogenuhličitan sodný; mužské pohlaví; Desoxycorticosterone; krysa rodu Rattus; cévní rezistence; Chlorides; zvířata; Bicarbonates; Hemodynamics; hemodynamika; hypertenze; deoxykortikosteron; Vascular Resistance; sodík; Sodium; Male; Animals